Beyond fusion towards IoT by way of open innovation: An investigation based on the Japanese machine tool industry 1975-2015 - Fumio Kodama; Tomoatsu Shibata (Journal of Open Innovation: Technology, Market, and Complexity, 2017)
In a last few decades, innovation research scholars proposed several new concepts, one after another, but independently, and in a chronological sequence: technology fusion; digital convergence; disruptive technology; open innovation; and IoT (Internet of Things). Each concept has its own explaining power for a certain innovation at a certain time period, but has obvious limitations. A basic question is, therefore, whether each of those proposed concepts is independent among them or inter-related dynamically, i.e. in what sequences? In order to answer this question, a specific industrial product, i.e. machine tools, is selected for our study. Although the machine tool is described as the mother machine, i.e. the machine of all the machinery, this industry experienced a drastic technological shift toward NC (numerically controlled) revolution around 1975. However, up until now, this industry continues to be a pivotal industry in modern and high-tech industrial era. By reviewing the technological history of the Japanese machine tool industry from 1975 to 2015, we observed several technological shifts even after the NC revolution, each of which can be explained with one of those concepts proposed in the last decades. We find a dynamic interrelationship among those concepts in the following sequence with the publication dates in parenthesis: disruptive technology (1997), technology fusion (1992), open innovation (2003), digital convergence (1996). We describe characteristics and analytical framework for IoT innovation that has gone beyond the traditional Schumpeterian formulation of innovation.
Keywords: 650